Chronic Intermittent Hypoxia Alters Local Respiratory Circuit Function at the Level of the preBötzinger Complex - Garcia, Alfredo J.; Zanella, Sebastien; Dashevskiy, Tatiana; Khan, Shakil A.; Khuu, Maggie A.; Prabhakar, Nanduri R.; Ramirez, Jan-Marino (Frontiers in Neuroscience, 2016)
Chronic intermittent hypoxia (CIH) is a common state experienced in several breathing disorders, including obstructive sleep apnea (OSA) and apneas of prematurity. Unraveling how CIH affects the CNS, and in turn how the CNS contributes to apneas is perhaps the most challenging task. The preBötzinger complex (preBötC) is a pre-motor respiratory network critical for inspiratory rhythm generation. Here, we test the hypothesis that CIH increases irregular output from the isolated preBötC, which can be mitigated by antioxidant treatment. Electrophysiological recordings from brainstem slices revealed that CIH enhanced burst-to-burst irregularity in period and/or amplitude. Irregularities represented a change in individual fidelity among preBötC neurons, and changed transmission from preBötC to the hypoglossal motor nucleus (XIIn), which resulted in increased transmission failure to XIIn. CIH increased the degree of lipid peroxidation in the preBötC and treatment with the antioxidant, 5,10,15,20-Tetrakis (1-methylpyridinium-4-yl)-21H,23H-porphyrin manganese(III) pentachloride (MnTMPyP), reduced CIH-mediated irregularities on the network rhythm and improved transmission of preBötC to the XIIn. These findings suggest that CIH promotes a pro-oxidant state that destabilizes rhythmogenesis originating from the preBötC and changes the local rhythm generating circuit which in turn, can lead to intermittent transmission failure to the XIIn. We propose that these CIH-mediated effects represent a part of the central mechanism that may perpetuate apneas and respiratory instability, which are hallmark traits in several dysautonomic conditions.